Pengolahan Limbah Air Rebusan Kedelai Menjadi Pupuk Organik Cair dengan Metode Batch Broth Fermentation di Desa Gunturmadu - Maria Ulfah; Resa Narulita; Ahmad Fatiin; Budiyono Budiyono; Akhmad Muhid; Nur Yasin; Sinta Fatimah; Akmal Amaliya; Syamaidzar Arban Jadid; Yunussita Fitri Alifia; Nurul Karimah; Dehli Syah Rizri; Syahrul Ihsan; Soffan Rizqi (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2024)
The use of chemical fertilizers in agricultural activities in Wonosobo can cause heavy metal contamination and soil damage on agricultural land. Gunturmadu Village is a village located in Wonosobo Regency with the majority of the population working as farmers. Based on observations, organic materials in the form of soybean boiled water waste in Gunturmadu Village have not been widely utilized. KPM students in Gunturmadu Village planned a socialization program for the practice of making liquid organic fertilizer from soybean boiled water waste using the batch broth fermentation method as an effort to realize a sustainable environment by preventing damage to soil nutrients, thereby increasing agricultural yields and increasing knowledge and skills in making liquid organic fertilizer. The activity was attended by 26 PKK RW members of Buaran Hamlet, Gunturmadu Village and 13 KPM students with direct counseling and practice methods. Data collection was in the form of pre-tests and post-tests. The research stages include the preparation, counseling, and evaluation stages. The results of the study showed an increase in knowledge and skills in making liquid organic fertilizer by 70.6% and a decrease in the percentage of misunderstanding by 70.96%.